INTERACTIVE METHODS AS A FACTOR IN DEVELOPING CRITICAL THINKING OF ELEMENTARY SCHOOL STUDENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the author describes the problem of forming students' critical ability, its theoretical foundations and content. Also, in the article, the influence of the role of interactive methods on the development of critical thinking skills of primary school studentsprofessional pedagogical features related to this process were discussed.